Pengaruh Customer Experience dan Kualitas layananTerhadap Loyalitas Pelanggan di UMKM Anda Cookies - Eni Sukmaningsih; Yulis Nurul Aini; Lina Budiarti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Companies in the Micro, Small, and Medium Enterprises (MSME) play a vital role in sustaining customers loyalty amid growing business competition. Anda Cookies as an MSME has delivered quality service and a positive shopping experience but continues to face difficulties in retaining repeat customers. This study aims to analyze the influence of customer experience and service quality on customer loyalty at Anda Cookies. This research adopted a quantitative approach, with data collected through questionnaires. Purposive sampling, was used to select 97 customers. The data were analyzed using multiple linear regression with SPSS version 25. The results showed that customer experience had a positive and significant effect on customer loyalty, meanwhile service quality had a positive but insignificant effect. Simultaneously, both variables significantly influenced customer loyalty. Based on the findings, it can be concluded that customer experience and service quality simultaneously have a positive and significant influence on customer loyalty at Anda Cookies. However, only customer experience shows a significant individual effect. It is recommended that the business continues to optimize customer interactions and service delivery in order to sustain and enhance customer loyalty.